2019
DOI: 10.1021/acsomega.9b03700
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of Tritium Diffusion in the Li3TaO4 Crystal

Abstract: Li3TaO4 with a high melting point, good thermal stability, and higher lithium content has become a possible choice for breeder materials, which have potential applications in future fusion reactors. Perfect and defect crystal models of Li3TaO4 are set up, and all of the tritium-diffusion pathways have been studied by the first-principles method. The activation energy barriers of different diffusion pathways are calculated and analyzed considering the pathway length and tritium–oxygen interactions. The obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…As a classic computational simulation method, first-principles molecular dynamics simulation calculates ionic interactions directly from first-principles, while requiring no fitting to the experimental data. It has been applied to KCl–LiCl, , CaO–CaSiO 3 , KF–NaF–AlF 3 –Al 2 O 3 , Li 3 TaO 4 , and FeAsS systems successfully.…”
Section: Introductionmentioning
confidence: 99%
“…As a classic computational simulation method, first-principles molecular dynamics simulation calculates ionic interactions directly from first-principles, while requiring no fitting to the experimental data. It has been applied to KCl–LiCl, , CaO–CaSiO 3 , KF–NaF–AlF 3 –Al 2 O 3 , Li 3 TaO 4 , and FeAsS systems successfully.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations performed for Li 3 TaO 4 , a potential tritium breeding material, indicated that tritium diffusion could decrease from 10 −9 m 2 •s −1 in a perfect crystal lattice to 10 −12 m 2 •s −1 for tritium hopping out of a Li vacancy. 37…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, it is interesting to note that vacancy defects could further slowdown tritium diffusion in breeding materials. Numerical simulations performed for Li 3 TaO 4 , a potential tritium breeding material, indicated that tritium diffusion could decrease from 10 –9 m 2 ·s –1 in a perfect crystal lattice to 10 –12 m 2 ·s –1 for tritium hopping out of a Li vacancy …”
Section: Resultsmentioning
confidence: 99%